OTONOMI DAERAH DALAM KONSEP HUBUNGAN PEMERINTAH PUSAT DAN PEMERINTAH DAERAH - Dian Mayasari; Ernest Violita; Karin Putri Prakasa; Sarmita Riskayanti (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The form of a unitary state which is now a final choice. Anyone who is now without exception must agree with the formula for the composition of a country that is now without exception. Various with the existence of a strengthening effort to strengthen the form of a state whose unity has now been carried out since our nation was independent. Likewise with the existence of a strategic and fundamentally structural problem that already exists in this country, it is hereby in the constitution that it has been carried out through a division of the territory of the Unitary State of the Republic of Indonesia even here into an area that has become (provinces and districts and city) which already has a basis of self-government to regulate also take care of things that are government affairs that have become their authority through the principles of decentralization. Even now that big house is in the form of the Unitary State of the Republic of Indonesia and a large family in the form of a nation, it must be managed properly in accordance with the existing religious, constitutional, legal and various principles such as local wisdom which is now recognized and guaranteed by the Constitution.